IMPLEMENTATION OF GREEN HISTORY IN HISTORY LEARNING IN SECONDARY SCHOOLS AS A BASIS FOR STUDENTS' ENVIRONMENTAL AWARENESS - Nadilla, Dewicca Fatma; Arisanty, Deasy; Angriani, Parida (International Conference On Social Science Education, 2023)
The environmental damage that occurs almost every year in South Kalimantan impacts many sectors, including the health sector, so efforts are needed to instil environmental awareness in the younger generation. One of the objectives of learning history in secondary schools in the independent curriculum is to develop moral, human and environmental values, and this is one of the basic foundations of why learning history can be used as a bridge of knowledge to internalize environmental awareness in students. This writing aims to see how learning history through a green history approach can help students develop environmental awareness integrated through local history material in South Kalimantan. This article was developed through a literature study by collecting various concepts and theories and previous research relevant to the green history approach and developing students' environmental awareness. In this paper, it can be concluded that the internalization of environmental awareness through implementing green history can be done with environmental content materials. Teachers' flexibility in the independent curriculum makes it easier to internalize material containing green History, both national History and local History.